Using the Learning Activities Survey to Examine Transformative Learning Experiences in Two Graduate Teacher Preparation Courses - Vicki Caruana; Kelli Woodrow; Luis Pérez (Park University, 2015)
The Learning Activities Survey (LAS) detected whether, and to what extent, a perspective transformation occurred during two graduate courses in teacher preparation. The LAS examined the types of learning identified as contributing to their transformation experiences. This study examined pre-service teachers' critical reflection of the course materials and learning experiences in a Capstone course in Reflective Teaching and a course in Universal Design for Learning (UDL). Results suggest that similar learning experiences were identified as triggering a perspective transformation. When learners have the opportunity to engage in critical reflection, they may more easily question their personal perspectives as a result.